Presumptive diagnosis of brucellosis and determination of risk factors for seropositivity among members of cattle keeping households in a high cattle traffi c area in the South Western region of Uganda - Arnold Ezama; Jean-Paul Gonzalez; Tesfaalem Tekleghiorghis Sebhatu; Tumwine Gabriel; Samuel Majalija; Francis Bajunirwe (Global Journal of Infectious Diseases and Clinical Research - Peertechz Publications, 2019)
Brucellosis is worldwide and affects human, cattle health and international trade. Human Brucella seroprevalence in Ugandan communities is not well known since most of the health centers are not able to screen for brucellosis. The study presumptively determined: seroprevalence, identifi ed risk factors associated with Brucella infection in cattle keeping household members and within their herds in Kyangyenyi sub county, Sheema district, South Western region of Uganda. A one-month cross-sectional study that used a simple two stage cluster sampling method was conducted where 216 households were randomly selected from 18 rural villages. Questionnaires were administered to household participants. Humans and cattle from same households were screened for Brucella antibodies using the Rose Bengal Test.